Proteasome inhibitor (MG132) rescues Nav1.5 protein content and the cardiac sodium current in dystrophin-deficient mdx5cv mice - Rougier, Jean-Sebastien; Gavillet, Bruno; Abriel, Hugues (Frontiers in Physiology, 2013)
The cardiac voltage-gated sodium channel, Nav1.5, plays a central role in cardiac excitability and impulse propagation and associates with the dystrophin multiprotein complex (DMC) at the lateral membrane of cardiomyocytes. It was previously shown that Nav1.5 protein content and the sodium current (INa) were both decreased in cardiomyocytes of dystrophin-deficient mdx5cv mice. In this study, wild-type (WT) and mdx5cv mice were treated for 7 days with the proteasome inhibitor MG132 (10 µg/Kg/24 h) using implanted osmotic mini pumps. MG132 rescued both the total amount of Nav1.5 protein and INa but, unlike in previous studies, de novo expression of dystrophin was not observed in skeletal or cardiac muscle. This study suggests that the reduced expression of Nav1.5 in dystrophin-deficient cells is dependent on proteasomal degradation.